Mekanisme Transmisi Pengetahuan dengan Modus Imperatif Kesiapan dan Kemampuan Penerapan Pembelajaran dalam Perspektif Pendidikan Islam - Sudar Kajin (PROGRESSA: Journal of Islamic Religious Instruction, 2019)
Grounding the transmission of knowledge by simplifying the learning process on real-world problems helps students maintain what is taught and remembers lessons learned when and when needed will have benefits and can be achieved using a variety of student-friendly teaching and learning methods that take into account interests, needs, and levels students. This article was written with the aim of studying the mechanism of knowledge transmission with the Readiness and Ability to Apply Learning Mode in the Islamic Education Perspective. The results of the discussion conclude that: 1) The concept of learning from teacher to student is popularly referred to as the 'Transmission' paradigm in learning and the process as a 'Transmission mechanism' with a different hierarchical Imperative mode; 2. In Islam, education is based on what Islamic ideals once held about educating all human beings rather than the narrow transmission of discursive knowledge. Islamic knowledge is the knowledge contained in the human body and the ways in which Muslims use it to archive, transmit, decode, and actualize religious knowledge based on a combination of imperative modes; 3) Islamic education aims to develop humans holistically, contrary to western education which focuses primarily on intellectual development. The main purpose of Islamic education is to reform and build human life and develop balanced relationships between individuals, communities and the world based on ethical concepts; 4) regardless of the frame of 'readiness to learn' or 'readiness for school', there is far more preparedness than this and far more that we can do to help everyone become more prepared to learn and overcome life.